2005
DOI: 10.1080/13556210500269366
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to chronic stress increases the locomotor response to cocaine and the basal levels of corticosterone in adolescent rats

Abstract: Repeated exposure to stress results in augmentation in the locomotor response to psychostimulant drugs. We investigated the locomotor response to a novel environment or cocaine [10 mg/kg, intraperitoneally (i.p.)] and basal corticosterone levels in male adolescent rats exposed to chronic restraint or variable stress. Animals in the chronic restraint group were restrained for 1 hour daily. The chronic variable stress protocol consisted of exposure to different stressors twice a day in random order. Chronic rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 31 publications
1
50
0
1
Order By: Relevance
“…In addition, rats with increased HPA reactivity induced by prenatal stress or by the absence of neonatal handling show an early decline of cognitive functions associated with the hippocampus, as well as increased propensity to self-administer drugs such as amphetamine and cocaine (55). In addition, exposure to both chronic restraint and unpredictable stress increased cocaine-induced locomotion and basal corticosterone plasma levels and chronic unpredictable stress also displayed the largest locomotor response following a challenge dose with cocaine compared with control and chronic restraint stress groups (60). Drug abuse is associated with changes in brain function and neurodegenerative processes, which, for some drugs, have been shown to be associated with the induction of apoptotic/necrotic cell death (Lepsch LB, , , , , Munhoz CD, Kawamoto EM, Lima LS, Scavone C, unpublished results).…”
Section: Stress Aging and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, rats with increased HPA reactivity induced by prenatal stress or by the absence of neonatal handling show an early decline of cognitive functions associated with the hippocampus, as well as increased propensity to self-administer drugs such as amphetamine and cocaine (55). In addition, exposure to both chronic restraint and unpredictable stress increased cocaine-induced locomotion and basal corticosterone plasma levels and chronic unpredictable stress also displayed the largest locomotor response following a challenge dose with cocaine compared with control and chronic restraint stress groups (60). Drug abuse is associated with changes in brain function and neurodegenerative processes, which, for some drugs, have been shown to be associated with the induction of apoptotic/necrotic cell death (Lepsch LB, , , , , Munhoz CD, Kawamoto EM, Lima LS, Scavone C, unpublished results).…”
Section: Stress Aging and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Following chronic cocaine selfadministration schedules, alterations to arousal-related dopaminergic and noradrenergic systems have been reported including increased densities of norepinephrine transporter binding in the hypothalamic nuclei and entorhinal cortex (Beveridge et al, 2005) as well as changes in the density of D1 and D2 receptors within striatal regions (Nader et al, 2002;Moore et al, 1998). Pre-exposure to cocaine in rats has also been associated with long-term sensitization of the corticotrophin-releasing factor (CRF) systems (Erb et al, 2003) and stress exposure has been shown to influence locomotor sensitization to cocaine (Lepsch et al, 2005;Haile et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Second, when exposed to a novel environment, LN and HN offspring exhibited more activity than NN offspring. High locomotor responsiveness in a novel environment results from a prior history of stress (31) and is associated with increased susceptibility for drug self-administration (39). Third, LN and HN offspring had exaggerated ACTH and Cort responses to restraint stress compared with NN offspring.…”
Section: Discussionmentioning
confidence: 99%